They stood their ground!’ – Professional Gangsters in South African Indian Society, 1940 - 1970 - Rachuene, Gose (My University, 2023)
This thesis is one part of a Creative PhD that investigates the emergence of a new breed of South African Indian gangsters in Durban and Johannesburg in the early apartheid period. The second part, existing as a separate creative text, is a screenplay for a feature film loosely based on dynamics and events present in the Durban Indian underworld of the 1950s. In the thesis I argue that while prominent ‘professional’ Indian gangsters were similar to other ‘non-white’ gangsters in certain respects (their self-fashioning in relation to gangster films, for one), these ‘gentlemen gangsters’ were different in terms of their high level of social and economic integration into Indian society. Focusing on the Crimson League in Durban and Sherief Khan’s gang in Johannesburg, this research comprises reconstructions from (and analysis of) interviews and written sources. It shows how these hustlers positioned themselves as protectors of the Indian community, but also cultivated reputations as punishers, capable of brutal violence if opposed.
Durban’s dominant gang in the early apartheid period, the Crimson League, a vigilante outfit that turned to illicit activities and thuggery. Chapter 4 looks at some of the adversaries that the League engaged and ultimately defeated, including the Salots and the Michael John Gang – I dissect the John murder trial to show how the Crimson League seemingly bent the law to their will. In Chapter 5, I move on to a description of Sherief Khan’s rise to power over rival Old Man Kajee in the Indian areas of